Computing essentials making IT work for you - O'Leary, Timothy J.; O'Leary, Linda I. (The O'Leary series, 2013)
A guide to computing concepts. It provides you with a learning solution focusing on important concepts of information technology. It gives students a relevant approach to the fundamental issues surrounding the world of computing through a balance between theory and applied learning of these important topics.